Biorefinery site selection using a stepwise biogeophysical and social analysis approach. (February 2017) - Martinkus, Natalie; Rijkhoff, Sanne A.M.; Hoard, Season A.; Shi, Wenping; Smith, Paul; Gaffney, Michael; Wolcott, Michael
Abstract: A key factor in the production of economically viable and environmentally sustainable biofuels is biorefinery site selection. Facility location analysis has traditionally been driven by access to feedstock, proximity to customers, and local incentives. While economic constraints will always be major factors in site selection, incorporating social metrics may further reduce the cost of constructing a biorefinery. A community's disposition toward a biorefinery project may significantly impact implementation success: grassroots support can lower implementation costs while opposition may increase the costs of permitting blockages and other scale-up delays. The proposed biorefinery siting tool improves upon previous research by incorporating site-specific biogeophysical measures and more complete and comprehensive social measures of community innovation and capacity for collective action. A refined biogeophysical analysis assesses pulp mills for their potential as repurposed biorefineries. The social asset components of site selection are greatly improved by enhancing and disaggregating key metrics through the use of multiple indicators of community collective action capacity and propensity for change. The refined measures are integrated into a biorefinery site-selection tool. Pulp mills that rank highly in both the biogeophysical and social asset measures may be considered more suitable candidates for repurpose into a biorefinery. This enriched methodology has been applied to biorefinery siting decisions in the U.S. Pacific Northwest region; however, it is suitable for applications to infrastructure development projects in any region of the U.S. Highlights: Stepwise approach to biorefinery siting decisions. Biogeophysical analysis of pulp mills performed through decision matrix. Social asset assessment measured through social, cultural, and human capital. High biogeophysical and social measures indicate potential biorefinery locations. Renewed integrated approach applicable to any region in U.S.